PENGEMBANGAN COMPUTER BASED TEST (CBT) BERBASIS ANDROID DI SMA NEGERI 8 SINJAI - Ahkamsyadid Ahkamsyadid Yusmaputra Salim; Farida Febriati; Nurhikmah H (LPPM Universitas Cipta Mandiri, 2024)
This development research aims to: (1) identify the needs of Based on Computer Based Test (CBT) based in Android in SMA Negeri 8 Sinjai. (2) Designing Computer Based Test (CBT) with Android based in SMA Negeri 8 Sinjai. (3) How to Receive the Validity of Personality & Practicality Computer Based Test (CBT) with Android based in SMA Negeri 8 Sinjai. This research refers to the steps of the development of the Alessi and Trollip development consisting of several stages, the planning, design, and development stage. The study was conducted at sinjai state high school with a combined study subject of 30 students and 1 homeroom teacher of class XII. The product is designed to consist of an alpha test carried out by 2 experts: media experts obtained an average 85% score on both qualifiers and content or materials obtained an average score of 91% so that computer based test can be tested cobakan over to see if small group trials are available, The big score scores an average of 95% on qualifications are very practical and the response of XII homeroom teachers the results are on qualifications very practical. This means it can be claimed that this android based test is very practical to use in the evaluation/test process of SMA Negeri 8 Sinjai. This research development produces computer computer bases (CBT) products in the form of apps already worth to be used for the process of learning evaluation in SMA Negeri 8 Sinjai.